2014
DOI: 10.1080/19419899.2013.876445
|View full text |Cite
|
Sign up to set email alerts
|

Sexual fluidity in young adult women and men: associations with sexual orientation and sexual identity development

Abstract: This research investigated sexual fluidity in attractions and sexual identity and associations with sexual orientation dimensions and sexual identity development in 199 (124 female, 75 male) US sexual minority young adults, ages 18-26 years. Participants completed an online questionnaire measuring sexual fluidity in attractions and sexual identity, sexual orientation dimensions (sexual identity, attractions, sexual behaviour) and sexual identity development. Sexual fluidity in attractions was reported by 64% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 41 publications
6
87
1
7
Order By: Relevance
“…It may represent change in attractions or sexual orientation identity toward or away from same-gender orientation. Previous research has found evidence of sexual fluidity among heterosexually-identified and other-gender attracted individuals (Dickson et al, 2003(Dickson et al, , 2013Katz-Wise, 2014;Kinnish et al, 2005;Mock & Eibach, 2012;Ott et al, 2011;Savin-Williams et al, 2012). This suggests that sexual fluidity is not limited to sexual minorities and may represent a coming out process for individuals who first indicate a heterosexual orientation but later indicate some element of samegender orientation (e.g., same-gender attractions, non-heterosexual sexual orientation identity).…”
Section: Sexual Fluidity and Gendermentioning
confidence: 87%
See 2 more Smart Citations
“…It may represent change in attractions or sexual orientation identity toward or away from same-gender orientation. Previous research has found evidence of sexual fluidity among heterosexually-identified and other-gender attracted individuals (Dickson et al, 2003(Dickson et al, , 2013Katz-Wise, 2014;Kinnish et al, 2005;Mock & Eibach, 2012;Ott et al, 2011;Savin-Williams et al, 2012). This suggests that sexual fluidity is not limited to sexual minorities and may represent a coming out process for individuals who first indicate a heterosexual orientation but later indicate some element of samegender orientation (e.g., same-gender attractions, non-heterosexual sexual orientation identity).…”
Section: Sexual Fluidity and Gendermentioning
confidence: 87%
“…Recently, a number of studies using both cross-sectional and longitudinal designs have begun to include both females and males and heterosexually-identified individuals in addition to sexual minorities. Whereas many of these studies have found greater frequency of sexual fluidity among females and sexual minorities, compared to males and heterosexual individuals (Dickson et al, 2003(Dickson et al, , 2013Mock & Eibach, 2012;Savin-Williams et al, 2012), some studies have found the opposite pattern, with sexual minority males indicating greater likelihood of sexual fluidity than sexual minority females (Rosario, Schrimshaw, Hunter, & Braun, 2006) or no significant gender difference among some sexual orientation groups (Katz-Wise, 2014;Kinnish et al, 2005;Ott et al, 2011). Now that it has been established that both females and males experience sexual fluidity, more research is needed to understand whether specific attitudes and beliefs are related to sexual fluidity.…”
Section: Sexual Fluidity and Gendermentioning
confidence: 92%
See 1 more Smart Citation
“…Unintended pregnancy for a SMW may be especially stressful due to the stigmatization and stress experienced by the population in general 63 and in the context of pregnancy. [64][65][66] Furthermore, for some SMW, especially those who identify as exclusively or mostly lesbian, unintended pregnancies may conflict with in-group normative behavioral expectations and invite stigmatizing attitudes from other lesbian-identified women, 37,67 which may increase the negative psychological impact of an unintended pregnancy. Most likely, both explanations are valid, but more research is needed to untangle the causal pathways and mechanisms linking unintended pregnancy to depression and hazardous drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown high levels of sexual fluidity and identity behavior incongruence (e.g., identifying as lesbian and engaging in heterosexual sex) among women. [35][36][37][38][39][40] For example, using nationally representative data, Xu et al showed that among adult women in the United States, 10% of currently identified lesbians and 70% of bisexual identified women had had a male sexual partner in the past 12 months. Furthermore, Xu et al showed that lesbians had a median of 2.9 male partners in their lifetime and bisexual women had a median of 17.6 male partners.…”
Section: Introductionmentioning
confidence: 99%